The Effectiveness of the Training Curriculum Program for Student Leaders in Health Promoting School in Suphan Buri Province - Pansri, Kamnuan; Suteeprasert, Tanin (Journal of Health Science of Thailand, 2017)
This quasi-experimental study which was aimed at determining the effectiveness of the training curriculum program for student leaders in health promoting school in Suphan Buri province. The samples were 90 students at grade 4-6 of primary school, Bang Pla Ma district, Suphan Buri province. They were divided into two groups: the experimental one and the control. Each group included 45 students. The experimental group received the training curriculum program from researcher’s integrated program for 3 days. The control group received the training curriculum formulation from a normal program of Ministry of Public Health. The program evaluation was carried out by questionnaires of knowledge, attitude, behaviors and satisfaction of training. Statistics used for data analysis were descriptive statistics: percentage, mean, and inferential statistic: t-test and paired t-test. It was found that after implementation for 3 months, the experimental group had mean scores of knowledge, attitude and behaviors significantly higher than before the experiment (p < 0.001) and higher than those of the control group. Whereas the control group did not show much improvements within the 3-month period. As as result, 82.2 percent of the trainees were very satisfied with the training curriculum formulation. Therefore, involved participants should provide the program to other health student leaders.